Independent Funded Media Organizations (IFMOs) and Citizen Engagement against Corruption in Nigeria - Solomon Abiodun Oyeleye; Eric Msughter Aondover; Charles Adewale (Economit Journal: Scientific Journal of Accountancy, Management and Finance, 2025)
Despite their many success stories in the social and political emancipation of Nigeria, the legacy newspapers have become less impactful in the pursuit of investigative journalism. This vacuum is now being exploited by independent funded media organisations (IFMOs), leading to a renaissance of the genre of journalism that has capacity to help society. A declining inability of the media to deal with corruption through investigative journalism, leaves the public with no hope for salvaging the national commonwealth from being embezzled, mismanaged or misappropriated either by public or private individuals. This is why the emergence of IFMOs to challenge the age-long hegemony of mainstream media practice, especially in the genre of investigative reporting, is worth investigating. This exploratory study, anchored on the disruptive innovation theory, used descriptive research method to look at Nigerian journalism practice using three purposively selected IFMOs: Wole Soyinka Centre for Investigative Journalism (WSCIJ), Centre for Journalism Innovation and Development (CJID) and Foundation for Investigative Journalism (FIJ). The study concludes that after a long time, investigative reporting is gaining more traction in the country but only thanks to the disruptive innovation employed by independent, funded media organisations and recommends this as a pragmatic model for a newspaper industry struggling to survive the various impacts of technology.